Recycling Oil Palm Industry Waste: Sustainable Solid Waste Treatment Utilizing Bioconversion Agent - Leo Hutri Wicaksono; M G Arrahim; A. R. Fadhillah (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
Oil palm is one of Indonesia's most important crops. Indonesia produces 47.180 million tonnes of CPO from an area of 14.858.300 hectares. When there are a lot of CPOs, it suggests there are a lot of wastes. EFB (Empty Fruit Bunch) is a significant biomass by-product of the oil palm industry. These cellulosic materials are relatively inexpensive feedstocks for ethanol synthesis and have no problem with the food supply because they are abundant and outside the human food chain. The principal by-product of the palm kernel oil extraction process is palm kernel meal (PKM). It's a high-fiber, medium-protein feed that's best suited for ruminant or rabbit consumption. EFB was once utilized as a fuel to generate steam at mills, whereas PKM was recycled into animal feed. Another option is to use bioconversion to control these wastes. The Black Soldier Fly (Hermetia illucens) larval (BSFL) is a worldwide insect whose larvae are notable for their capacity to eat a variety of organic wastes. The BSFL were housed in a container and fed EFB and PKM. There were two different treatment options (3 replication per treatments). Each treatment contained 200 larvae and 400 grams of food. The research lasted 18 days. The larvae were collected on the 18th day, and container were measured. Treatment 1 (EFB) have average 9,46% waste consumption, and Treatment 2 (PKM) have 23,14% waste consumption on average.